René Laurentino Miní Rodríguez Cobre and Carlos Manuel Miní Llorens, first dentists in Lajas, Cienfuegos - Perla Margarita Pacheco Morffi; Melissa Villavicencio Nerey; Ana Belkys Hernández Millán; José Danilo Pacheco González; Félix Alberto Companioni Landín (Medisur)
Many events and personalities have been part of the Stomatology historical evolution in Cienfuegos. This article aims to describe the significant events in life and work of René Laurentino Miní Rodríguez Cobre and Carlos Manuel Miní Llorens doctors. A historical research was carried out, using techniques such as documentary review and in-depth oral interviews, with testimonies from key informants as the primary source for obtaining information. Historical legal documents were also consulted. René Miní, once graduated in the United States, returned to his native Lajas to practice there as the first official dentist. Said legacy was assumed by his son, follower of his father's work, graduated from the Havana University. They remained in Cuba until 1972, when the whole family emigrated to Spain. The study of the life and work of these Stomatology professionals allowed knowing and patenting historical data about the beginnings of this in Cienfuegos, especially in Lajas. Both made available to the population the most advanced in this branch of science at the beginning of the 20th century.